Symmetry Reduction of Molecular Shape of Cationic Chromophores for High-Performance Terahertz Generators - Yoon, Ga Eun; Kim, Dong Joo; Park, Yu Jin; Kim, Chaeyoon; Kim, Seung Jun; Shin, Bong Rim; Lee, Yun Sang; Lee, Chae Won; Park, Jung Wook; Yu, In Cheol; Yoon, Woojin; Yun, Hoseop; et al. (Advanced Optical Materials, 2024)
The symmetry reduction of molecular shape of cationic chromophores as a design strategy to develop organic terahertz (THz) generators is used. Electron donating group (EDG) with an asymmetric shape is introduced into two types of cationic styryl-quinolinium chromophores, leading to the development of several novel non-centrosymmetric crystals with high macroscopic optical nonlinearity. In contrast, when an EDG with a symmetric shape is introduced, centrosymmetric crystal structure is obtained in all investigated crystals. For THz wave generation, crystals based on asymmetrically shaped EDG exhibit several optimal crystal characteristics, including a plate-shape morphology, a large size, and an in-plane polar axis. Furthermore, over the entire range of molecular phonon vibrations, 0.5–4 THz, the steric hindrance group in the asymmetrically shaped EDG has a strong influence on the suppression of THz phonon vibrations, leading to a low THz absorption coefficient. The crystals based on asymmetrically shaped EDG generate an ≈40 times stronger THz electric field than the inorganic ZnTe crystal and very broad THz spectra, extending up to 16 THz. Thus, the symmetry reduction of the molecular shape of cationic chromophores through the introduction of an asymmetrically shaped EDG is an effective design approach for the development of novel organic THz crystals.
Keywords: Cationics; Electron-donating group; Molecular shapes; Organic crystal; Organics; Performance; Phonon vibrations; Symmetry reduction; Tera Hertz; Terahertz photonics; nonlinear optics; organic crystals; terahertz photonics